2000
DOI: 10.1152/ajpheart.2000.279.4.h1571
|View full text |Cite
|
Sign up to set email alerts
|

Three-week neonatal hypoxia reduces blood CGRP and causes persistent pulmonary hypertension in rats

Abstract: To increase understanding of persistent pulmonary hypertension, we examined chronic pulmonary effects of hypoxia at birth and their relationships with immunoreactive levels of the potent vasodilator, calcitonin gene-related peptide (CGRP). Rats were born in 10% hypobaric hypoxia, where they remained for 1-2 days, or in 15% hypoxia, where they remained for 21 days. All were then reared in normoxia for 3 mo followed by reexposure to 10% hypoxia for 7 days (H-->H) or continued normoxia (H-->N); age-matched normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Reversing effects on vascular remodeling of another ROCK inhibitor, fasudil, have been previously reported in adult rats with monocrotaline-induced chronic PHT (1,40). To our knowledge, this is the first study to examine the reversing effects of ROCK inhibition on vascular remodeling in the immature animal, which may be more resistant to reversal than adults (8,17,29,30,47,52,62) and the first to document normalized RV function as a consequence of sustained rescue treatment with a ROCK inhibitor. Our observation that sustained reduction of PVR and of RVSP were dependent upon ongoing inhibition of ROCK activity with Y-27632 are further in keeping with ROCK-mediated pulmonary vasoconstriction being the main determinant of raised pulmonary vascular pressure and resistance secondary to chronic hypoxia (38,58).…”
Section: Discussionmentioning
confidence: 60%
“…Reversing effects on vascular remodeling of another ROCK inhibitor, fasudil, have been previously reported in adult rats with monocrotaline-induced chronic PHT (1,40). To our knowledge, this is the first study to examine the reversing effects of ROCK inhibition on vascular remodeling in the immature animal, which may be more resistant to reversal than adults (8,17,29,30,47,52,62) and the first to document normalized RV function as a consequence of sustained rescue treatment with a ROCK inhibitor. Our observation that sustained reduction of PVR and of RVSP were dependent upon ongoing inhibition of ROCK activity with Y-27632 are further in keeping with ROCK-mediated pulmonary vasoconstriction being the main determinant of raised pulmonary vascular pressure and resistance secondary to chronic hypoxia (38,58).…”
Section: Discussionmentioning
confidence: 60%
“…Exposure to perinatal hypoxia and the development of pulmonary vasoconstriction and hypertension later in adulthood have been witnessed in many studies [41][42][43]. Hakim et al found that adult rats exposed to hypoxia in the perinatal period had increased reactivity to hypoxia and elevated pulmonary vascular resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been localized with immunocytochemistry and in situ hybridization to airway epithelial neuroendocrine cells and interstitial ganglia (20) and also by immunocytochemistry to epithelial and vascular networks (17,36). We found early on that CGRP was significantly reduced in left ventricular blood of rats with HPH (18,34) and persistent PH (21), contributing to an imbalance between vasoconstrictors and vasodilators. We further found that exogenous CGRP prevents the development of HPH and reverses existing HPH via the CGRP type 1 receptor in rats (19,34).…”
mentioning
confidence: 91%